Prenatal and pubertal exposure to 17α-ethinylestradiol disrupts folliculogenesis and promotes morphophysiological changes in ovaries of old gerbils (Meriones unguiculatus) - De Souza, Vinícius Gonçalves; Bandeira, Laura Borges; Souza, Nátaly Caroline Silva E; Taboga, Sebastião Roberto [UNESP]; Martins, Tracy Martina Marques; Silva Perez, Ana Paula (Cambridge University Press (CUP), 2020)
17α-Ethinylestradiol is an endocrine-disrupting chemical that make up most contraceptive pills and can be found in the environment. Exposure to ethinylestradiol in different development periods may promote changes in morphophysiological parameters of reproductive and endocrine organs. Considering that the effects of low doses (15 μg/kg/day) of ethinylestradiol in ovaries from 12-month-old female gerbils (Meriones unguiculatus) were investigated. Four experimental groups used were control (without treatment), EE/PRE (treated from the 18th to the 22nd gestational day), EE/PUB (treated from the 42nd to the 49th day of life), and EE/PRE-PUB (treated in the both periods). The animals were euthanized at 12 months. Testosterone and 17β-estradiol levels were measured. The ovaries were stained with Hematoxylin and Eosin, Periodic Acid Schiff, and Gomori's Trichome. The follicles, corpus luteum, interstitial gland, lipofuscin, ovarian epithelium, and tunica albuginea were analyzed. Estradiol was higher in EE/PRE and EE/PUB groups, while testosterone was higher only in EE/PUB group. The main changes in follicle count occurred in EE/PUB and EE/PRE-PUB groups, with higher primordial follicle count and lower maturation of follicles. The corpus luteum was more evident in EE/PRE group. No differences were found in atretic follicles count. A higher area occupied by interstitial gland cells and lipofuscin deposit in these cells was noted in EE/PUB and EE/PRE-PUB groups. Higher epithelium height and thicker tunic albuginea were showed in treated groups. These results suggest that exposure to doses of EE2 in prenatal and pubertal periods of the development leads to morphological changes in senile ovaries.
Keywords: contraceptive agents; endocrine disruptors; Gerbillinae; Keywords; ovary